Aging in Place With a Spouse in Need: Neighborhood Cohesion and Older Adult Spouses' Physical and Mental Health. (December 2021) - Lee, Kyuho; Marier, Patrik
This study examines the association of perceived neighborhood cohesion (NC) with older adults' health and the buffering effects of NC against the negative effects of spousal caregiving on health. Data of 3329 community-living older adults living with a spouse in need of care from the Health and Retirement Study were collected at two time-points. Multiple regression analyses were computed for each of the four health outcomes. For men, NC predicted fewer depressive symptoms and better cognition. NC buffered the negative effect of providing activities of daily living (ADL) help to the wife on cognition. For women, NC predicted fewer depressive symptoms and better cognition. NC buffered the negative effect of providing ADL help to the husband on ADL difficulties. The results accentuate the importance of residency location for older adults' physical and mental health. The health benefits of NC may have more implications for older adults providing spousal care.